Avaliação de diferentes tipos de secagem da casca de jabuticaba (Myrciaria cauliflora) para preservação dos compostos bioativos - Saibert, Claudinei Luiz (2022)
The species Myrciaria cauliflora Berg. known as jabuticabeira belongs to the Myrtaceae family. The most explored property is the high antioxidant potential that jabuticaba presents, being related to the amount of phenolic compounds, mainly anthocyanins. Thus, the objective of this work was to define which drying method is the most viable for obtaining jabuticaba peel powder, in order to preserve the phenolic compounds, and which can be used in nutraceutical and food compositions. The peels were dried in a static dryer with forced air circulation, lyophilizer and fluidized bed, then all material was crushed and the analyzes performed were: apparent and compacted density, humidity, pH determination and visual analysis. Crude ethanolic extracts were prepared to evaluate the antioxidant activity and antimicrobial activity against the microorganisms S. aureus, E. coli and C. albicans. Fluidized bed drying was evaluated with experiments using an experimental design 22 with duplicate. By analyzing all the data, the efficiency of the drying process together with the properties of the final product, the drying processes in a freeze dryer are subjected to temperature - 50 °C pressures up to 205 mmHg, in a fluidized bed under a volumetric flow of 600 m3 /h and 25°C proved to be the best drying conditions for the purpose of preserving the substances, with a concentration that inhibits the proliferation of cell cultures by 50% IC50 29.7 µg/mL, however, they did not effectively influence the antimicrobial activity. Thus, fluidized bed drying stands out as a viable technique, it provides an environment in a state of incoming air flow for the material to be dried, control of variables, preservation of substances and effective for large-scale production, adding value to the jabuticaba by-product, with potential application in the pharmaceutical industry, as tablet coating and in the composition of nutraceuticals.